Mapping Systematic Reviews on Forensic Psychiatric Care: A Systematic Review Identifying Knowledge Gaps - Howner, Katarina; Andiné, Peter; Bertilsson, Göran; Hultcrantz, Monica; Lindström, Eva; Mowafi, Frida; Snellman, Alexandra; Hofvander, Björn (Frontiers in Psychiatry, 2018)
Background Forensic psychiatric care treats mentally disordered offenders who suffer mainly from psychotic disorders, although comorbidities such as personality disorders, neurodevelopmental disorders, and substance abuse are common. A large proportion of these patients have committed violent crimes. Their care is involuntary, and their caregivers’ mission is complex: not only to rehabilitate the patient, but also to consider their risk for reoffending and their risk to society. The objective of this overview of systematic reviews is to identify, appraise, and summarize the existing knowledge in forensic psychiatric care and identify gaps in that knowledge that require further research. Methods We undertook a systematic literature search for systematic reviews in five defined domains considered important daily clinical practice in the forensic psychiatric care: (1) diagnostic assessment and risk assessments; (2) pharmacological treatment; (3) psychological interventions; (4) psychosocial interventions, rehabilitation, and habilitation; and (5) restraint interventions. The target population was mentally disordered offenders (forensic psychiatric patients aged >15 years). Each abstract and full text review was assessed by two of the authors. Relevant reviews then were assessed for bias, and those with moderate or low risk of bias were included. Results Of 38 systematic reviews meeting the inclusion criteria, only four had a moderate risk of bias. Two aimed to incorporate as many aspects of forensic psychiatric care as possible, one investigated non-pharmacological interventions to reduce aggression in forensic psychiatric care, and one focused on women with intellectual disabilities in forensic care. However, most of the primary studies included in the reviews had high risks of bias, and therefore, no conclusions could be drawn. All of our identified domains must be considered knowledge gaps. Conclusion We could not answer any of our research questions within the five domains because of the high risk of bias in the primary studies in the identified systematic reviews. There is an urgent need for more research on forensic psychiatric care since all of our studied domains were considered knowledge gaps.